2020
DOI: 10.1021/acsanm.0c01360
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/WS2 Nanodisk Van der Waals Heterostructures on Plasmonic Ag Nanoparticle-Embedded Silica Metafilms for High-Performance Photodetectors

Abstract: Coupling plasmons and excitons provide a promising approach to enhance the performance of photodetectors based on two-dimensional (2D) atomic layer heterostructures. Herein, we report a nanohybrid photodetector achieved by transferring a nonmetallic plasmonic WS2 nanodisk/graphene van der Waal (vdW) heterostructure grown using chemical vapor deposition, on metallic plasmonic Ag nanoparticles embedded in 20 nm thick silica (AgNP-metafilm) fabricated using in situ Ag and Si evaporation through a shadow mask. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…The graphene was synthesized using chemical vapor deposition (CVD) on commercial copper foils (Sigma-Aldrich) at ∼1000 °C. The details of graphene growth and transfer were reported in previous works [21,22]. In the third step, the CNT film was transferred on top of graphene to form the 3D CNT/Gr nanohybrid (figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
“…The graphene was synthesized using chemical vapor deposition (CVD) on commercial copper foils (Sigma-Aldrich) at ∼1000 °C. The details of graphene growth and transfer were reported in previous works [21,22]. In the third step, the CNT film was transferred on top of graphene to form the 3D CNT/Gr nanohybrid (figure 1(b)).…”
Section: Methodsmentioning
confidence: 99%
“…Alamri et al reported a 5 times increase in the responsivity of graphene/WS 2 nanodisk PDs by using a Ag metafilm under an illumination of 450 nm. 33 Moreover, a plasmonic-enhanced photoresponse was observed in a Ag-WS 2 /Si heterojunction by Patel and coauthors. 34 The above reports suggest that some studies have been carried out to investigate the effect of Au and Ag NPs on visible or IR PDs fabricated on graphene and TMDCs.…”
Section: Introductionmentioning
confidence: 95%
“…Besides these, plasmonic-enhanced heterostructures have also been reported. Alamri et al reported a 5 times increase in the responsivity of graphene/WS 2 nanodisk PDs by using a Ag metafilm under an illumination of 450 nm . Moreover, a plasmonic-enhanced photoresponse was observed in a Ag-WS 2 /Si heterojunction by Patel and coauthors .…”
Section: Introductionmentioning
confidence: 95%
“…Plasmonic metal nanostructures may be placed in proximity to nanohybrids photodetectors for the benefit of light trapping. [ 153 ] A recent work by Alamri et al [ 154 ] combines the plasmonic effects from TMD nanodiscs grown on graphene and Ag nanoparticles deposited using an in vacuo process to obtain an enhanced photoresponse.…”
Section: Recent Progress In Nanohybrid Photodetectorsmentioning
confidence: 99%